A Tumultuous Change: The Restructuring of the Meatpacking Industry and Its Effects Upon Austin, Minnesota 1985-2011 - Christiansen, Tyler (My University, 2011)
The 1980s was a turbulent time for the country and especially the meatpacking industry. During this time, the economy was in a deep recession, with unemployment figures reaching levels not seen since the Great Depression. In the midst of this chaos, numerous changes were occurring in the meatpacking industry, most notably the restructuring of the American unions. As numerous meatpacking plants were closing and reopening with non-union workforces, a local union in a small southern Minnesota meatpacking town decided that it would not give into the demands of corporate America. This struggle against the Geo. A. Hormel & Company (Hormel) would turn into a David and Goliath like struggle, eventually capturing the audience of not only the town, but also the state and the nation. As the struggle progressed, the people of this small union town would not only learn the first hand effects of the meatpacking industries' changing mentalities, but also the lasting effects of their struggle.
Keywords: Austin (Minn.)--Economic conditions--History; Meat industry and trade--Minnesota--Austin; United Packinghouse, Food, and Allied Workers. Local 9 (Austin, Minn.); Geo. A. Hormel & Company Strike, Austin, Minn., 1985-1986; Packing-houses--Minnesota--Austin; Strikes and lockouts--Packing-house workers--Minnesota--Austin